Effects of Positive Affirmations and Journaling On Self-Compassion among Parolees at Bapas Kelas II Bukittinggi - Bayu Satria; Tuti Rahmi (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study aims to examine the effectiveness of positive affirmations and journaling in enhancing self-compassion among parolees undergoing a reintegration program. The study employed a quasi-experimental design with a pretest–posttest control group design and involved 30 participants divided into three groups: Group A (positive affirmations), Group B (journaling), and Group C (control). Self-compassion levels were measured using the Self- Compassion Scale (SCS) before and after the intervention. Group A and B received the intervention over four sessions spanning eight weeks, while the control group followed standard reintegration procedures without additional psychological intervention. Results of the Analysis of Covariance (ANCOVA) indicated significant differences among the groups after controlling for pretest scores. A Bonferroni post-hoc test indicated that only Group B (journaling intervention) showed a significant difference compared to the control group, whereas the positive affirmation did not demonstrate a statistically significant effect. These findings suggest that journaling is more effective in enhancing self-compassion in the context of this study, while positive affirmations only showed a descriptive improvement.